Historical estimates of curvina (Cynoscion acoupa) growth and mortality parameters in Lake Maracaibo, Venezuela - Cristina Morales, Isabel; Ferrer Montaño, Orlando José (Ciencia)
This paper addressed the historical trend in growth and mortality parameters of curvina (Cynoscion acoupa) in Lake Maracaibo based on data from artisanal commercial fisheries collected in 1969-1970, 1985-1986 and 2009. Mean total length (TL) of captures of curvina diminished 31 per cent in 25 years (TL Ó sd1969-1970 = 49.0 Ó 3.9 cm TL; TL Ó sd1985-1986 = 48.7 Ó 4.1 cm TL; TL Ó sd2009 = 33.7 Ó 7.57 cm TL), indicating that the fishery was sustained by juveniles and preadults (length of first maturity = 40 cm TL). Although natural mortality (M) remained constant between 1985-1986 and 2009 (M1985-1986 = 0.53 year”“1; M2009 = 0.56 year”“1), the significant increasing of fishing mortality (F) (F1985-1986 = 0.58 year”“1; F2009 = 3.76 year”“1) corroborated that the fishing intensity exerted in the zone was high. Mesh size lesser than 8.89 cm should be banned from the curvina fishery to ensure that fish have spawned at least once before being caught. This would avoid curvina recruitment overfishing.